Pozyskiwanie i energetyczne zagospodarowanie biomasy rolniczej a zrównoważony rozwój w świetle prawa Unii Europejskiej - Błażejewska, Kamila (Wydawnictwo Naukowe UAM, 2012)
The growing demand for biomass for energy purposes within the EU member states may cause multiple effects of different nature (social, environmental, economic) and scope (local, regional and global). In the paper, an attempt is made to answer the question on how the EU legislation ensures sustainable production and use of agricultural biomass for energy purposes. The first part of the paper provides an outline of the sustainability criteria for biofuels and bioliquids. The second part describes the EU environmental and rural legislation. The Common Agricultural Policy is considered a relatively efficient tool securing sustainable production of biomass within the EU territory. The third part is dedicated to the sustainability criteria certification schemes, with a special focus on the German certification mechanisms. It has been pointed out that there is still a pending need to include solid and gaseous biomass into the binding sustainability schemes, and to widen their scope, especially by integrating the important social and economic issues with regard to biomass originating from the third countries. The paper ends with a conclusion that the current EU legislation is not sufficient to ensure a sustainable production of energy production from agricultural biomass.

L’aumento della domanda di biomassa utilizzata per la produzione di energia negli Stati membri dell’Unione europea potrebbe portare a conseguenze negative di carattere sociale, ambientale ed economico su scala globale. L’autrice cerca di rispondere alla domanda in che misura le regolazioni giuridiche dell’Unione europea in vigore garantiscelo sfruttamento energetico della biomassa agricola in linea con lo sviluppo sostenibile. Nella prima parte dell’articolo viene sollevata la questione dei criteri di sviluppo sostenibile per i biocarburanti e i bioliquidi. La seconda parte delle considerazioni siriferisce alle norme agro-ambientali in vigore nel quadro della politica agricola comune. In seguito si discutono i sistemi di attestazione della conformità con i criteri di sviluppo sostenibile sull’esempio dell’Unione europea e della Germania. L’autrice fa notare che le prescrizioni vincolanti per la biomassa solida e gassosa continuano a mancare, e che anche i criteri di sviluppo sostenibile in vigore per i iocarburanti e i bioliquidi non tengono conto degli importanti problemi socioeconomici presenti nei paesi terzi in relazione ad una domanda crescente di biomassa nell’Ue. Perciò, le regolazioni europee in vigore sulla qualità di biomassa in vigore, specie in riferimento alla sua origine, non possono essere ritenute soddisfacenti.